Wind pressure resistant high-conductivity steel-cored aluminum strand material and method for manufacturing the same
Patent Information
- Application Number
- CN202611355261.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本申请提供了一种抗风压高导电率钢芯铝绞线材料及其制备方法,解决了层间耦合状态由绞合节距单一参数固定、层间耗能须以增大绞线外径为代价、以及承力芯与内层铝丝接触部位在往复微幅位移下锌层被磨穿这三方面的问题
[0004]本申请提供了一种抗风压高导电率钢芯铝绞线材料及其制备方法,解决了层间耦合状态由绞合节距单一参数固定、层间耗能须以增大绞线外径为代价、以及承力芯与内层铝丝接触部位在往复微幅位移下锌层被磨穿这三方面的问题。本申请在承力芯的镀层包络以内构造随滑移量改变法向力的接触界面,使绞线外径与层间耗能行程互不牵连,并使爬升所生扭矩与绞线在张力下的退扭趋势相抵。
Smart Images

Figure CN122889484A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of overhead conductor technology, and in particular to a wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material and its preparation method. Background Technology
[0002] Overhead transmission line conductors bear both static wind pressure and wind-induced vibration during their service life. Static wind pressure acts on the windward projection surface of the conductor, is transmitted to the tower via strands, and its magnitude increases linearly with the conductor's outer diameter. Wind-induced vibration is divided into two types: high-frequency, low-amplitude micro-vibration and low-frequency, high-amplitude galloping. Micro-vibration has a frequency between several hertz and one hundred hertz, and its amplitude usually does not exceed the conductor diameter, occurring for 30% to 50% of the year. Galloping is excited by the lift generated by horizontal wind acting on an asymmetrical cross-section and is a self-excited vibration, with the vertical and torsional coupling induced by aerodynamic negative damping in the torsional direction. To balance current carrying capacity and tensile strength, these conductors generally use galvanized steel wire or aluminum-clad steel wire as the load-bearing core, with layered, reverse-stranded aluminum monofilaments on the outer periphery as the current-carrying layer. The aluminum side is made into monofilaments through melt purification, continuous casting and rolling, heat treatment, and multiple cold drawing processes. For wind-induced vibration, existing technologies have developed two approaches. One approach is to install vibration dampers and damping wires outside the conductor, relying on external components to dissipate the mechanical energy of the circuit system. Another approach is to enable the conductor itself to dissipate energy. This is achieved by leaving interlayer gaps between the steel core and the inner aluminum wires, as well as between the layers of aluminum wires. These gaps are filled with lubricating grease, or by using trapezoidal or SZ-shaped aluminum monofilaments to create the gaps. This prevents forced radial contact between the layers under operating loads, allowing the layers to dissipate energy by shifting relative to each other along the gaps when the conductor bends. A parallel parameter approach is to adjust the stranding pitch. Increasing the pitch increases the interlayer locking force to reduce relative movement, while decreasing the pitch or using a variable pitch allows for a certain amount of relative movement between layers to achieve damping.
[0003] The existing techniques described above suffer from the following problems in several technical aspects: Leaving interlayer gaps increases the outer diameter of the stranded wire for the same conductive cross-section, thus expanding the windward projection area. This increases the static wind pressure load at this stage, which overlaps with the load borne by the load core. During the laying process, the interlayer gaps collapse after being squeezed by the traction wheel and the wire spool. The gaps formed by the SZ-shaped monofilaments disappear after collapse, altering the relative misalignment between layers. Furthermore, the surface flatness decreases after the trapezoidal monofilaments are stranded, creating conditions for tip discharge on the outer surface of the stranded wire at high voltage levels. The lubricating grease injected into the gaps migrates and is lost axially under long-term temperature cycling and vibration conditions, causing changes in the interlayer friction state during service life. The method of adjusting interlayer coupling by stranding pitch only takes a fixed compromise value for one parameter. Both locking and energy dissipation requirements share this parameter. If the pitch is too large, the relative motion between layers is insufficient, and the energy dissipation stroke is limited. If the pitch is too small, the interlayer locking force is insufficient, and the interlayer anti-slip capability under gusts and static wind pressure is limited. Both cannot be achieved simultaneously on the same conductor. The contact area between the galvanized steel core and the inner aluminum wire undergoes fretting wear under the reciprocating micro-amplitude displacement caused by micro-wind vibration. After the zinc layer is worn through, the steel base is exposed, and the cross-section of the steel wire thins under rainwater intrusion conditions. Summary of the Invention
[0004] This application provides a wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material and its preparation method, solving three problems: the interlayer coupling state is fixed by a single parameter of stranding pitch; interlayer energy dissipation requires increasing the outer diameter of the stranded wire; and the zinc layer is worn through at the contact point between the load-bearing core and the inner aluminum wire under reciprocating micro-displacement. This application constructs a contact interface within the coating envelope of the load-bearing core, where the normal force changes with the amount of slippage. This ensures that the outer diameter of the stranded wire and the interlayer energy dissipation stroke are independent, and that the torque generated during climbing counteracts the tendency of the stranded wire to twist under tension.
[0005] In one aspect, this application provides a wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material, comprising a steel core and three layers of aluminum monofilaments stranded around the outer periphery of the steel core; the steel core includes one central galvanized steel wire and six wedge-lift steel wires, the zinc layer mass per unit area of the wedge-lift steel wires being 240 g / m² to 280 g / m²; the conductivity of the aluminum monofilaments being 60.5% IACS to 61.5% IACS, and the compaction coefficient of the three layers of aluminum monofilaments being 0.92 to 0.94; the surface of the wedge-lift steel wires is provided with grooves of a depth of 15 μm to 25 μm, the grooves being composed of a gently sloping surface and a steep back wall, the angle between the gently sloping surface and the axis of the wedge-lift steel wire being [missing information]. The angle is 6.0° to 9.0°. The top of the gentle slope is a passivated bearing surface with a transition arc radius of 1.5mm to 2.5mm. The groove includes a positive group in which the gentle slope descends in the positive axial direction and a reverse group in which the gentle slope descends in the negative axial direction. The positive group and the reverse group are arranged alternately in the axial direction with a period of 2.5mm to 3.5mm and are staggered circumferentially by 40° to 50°. The ratio of the total area of the passivated bearing surface to the surface area of the wedge-lifting wire is 4.0% to 8.0%. The spiral tendency of the gentle slope is opposite to the twisting direction of the adjacent layer of aluminum monofilaments. The aluminum monofilaments adjacent to the groove are provided with aluminum protrusions embedded in the groove.
[0006] Secondly, this application provides a method for preparing a wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material, comprising the following steps: pickling, phosphating, and multi-pass drawing of steel wire rod with a carbon mass fraction of 0.80% to 0.84%; hot-dip galvanizing the drawn steel wire rod in zinc bath at 455℃ and wiping with an air knife to obtain a reference galvanized steel wire with a zinc layer mass of 240g / m² to 280g / m² per unit area; rolling the reference galvanized steel wire through a rolling wheel with circumferential cutting grooves at a linear load of 180N / mm to create grooves with a depth of 15μm to 25μm, which are arranged alternately in positive and negative groups, to obtain a bidirectional wedge-lift textured steel wire; and performing a secondary finishing rolling on the bidirectional wedge-lift textured steel wire at a linear load of 60N / mm to process the top of the gently sloping surface of the grooves into a passivated bearing. The surface is pressed to obtain wedge-lift steel wire; a boron-aluminum master alloy is added to molten aluminum at 735°C and kept at this temperature with stirring. The molten aluminum with the added boron-aluminum master alloy is then refined with argon gas to remove hydrogen and slag. The refined molten aluminum is then continuously cast and rolled to obtain an aluminum rod; the aluminum rod is subjected to an over-aging treatment at 360°C for 8 hours, and the over-aging aluminum rod is then subjected to multiple cold drawing passes to obtain an aluminum monofilament; one galvanized steel wire at the center is twisted with six wedge-lift steel wires to form a steel core. The aluminum monofilament is twisted in three layers and tightly pressed against the outer periphery of the steel core. The spiral tendency of the gently inclined surface is opposite to the twisting direction of the adjacent layer of aluminum monofilament. The aluminum monofilament is plastically filled in the groove to form aluminum protrusions, resulting in a wedge-lift meshing wire blank; the wedge-lift meshing wire blank is subjected to a stabilization aging treatment at 180°C for 3 hours to obtain a steel-core aluminum stranded wire.
[0007] This application replaces the interlayer gap with a wedge-shaped contact interface formed by a gently sloping surface. The interlayer frictional resistance increases with the relative slip, and the locking and energy dissipation requirements no longer share the same hinge pitch parameter. Under a gently sloping surface angle of 7.5°, the locking threshold slip is 4.56 μm. A 1 μm to 4 μm interlayer slip caused by aerodynamic vibrations at the suspension clamp outlet falls into the energy dissipation zone, while a 10 μm to 50 μm interlayer slip caused by gusts and static wind pressure falls into the locking zone. The single-cycle energy dissipation at a single contact point with a slip amplitude of 2.0 μm is reduced compared to the situation without the sloping surface. J rises to J, at a slip amplitude of 4.0 μm, is... J rises to J. The logarithmic attenuation rate of the finished stranded wire changed from 0.0061 for conventional compacted steel-cored aluminum stranded wire of the same specification to 0.0142, and the number of cycles of repeated bending at the wire clamp exit until the first strand breaks changed from... Next change The groove depth of 20μm is within the 36.4μm coating corresponding to a zinc layer mass of 260g / m² per unit area. The passivated pressure-bearing surface is flush with the maximum outer circumference of the steel wire. The finished outer diameter is 26.82mm, the same as that of the same specification of non-woven compacted stranded wire. The wind load per unit length at a design wind speed of 30m / s is 16.59N / m. For the same energy consumption level, the interlayer gap scheme has an outer diameter of 28.4mm and a wind load of 17.58N / m. This application is 5.63% lower in this aspect. Interlayer energy consumption does not depend on interlayer cavities, and the damping attenuation caused by gap collapse and grease loss no longer occurs. The residual zinc layer at the bottom of the groove is 16.4μm. Combined with the passivated pressure-bearing surface, the nominal contact pressure in the locked state is 197MPa, which is one-third of the zinc layer fracturing threshold of 600MPa. After 1000 hours of salt spray testing, the coating integrity rate is 96%, while that of the unpassivated control is 71%. After boronizing to remove impurities and over-aging cold drawing, the aluminum monofilament has a conductivity of 61.0% IACS, a tensile strength of 178MPa, and a DC resistance of 0.0724Ω / km at 20℃. The interlayer locking ability is no longer determined by the steel ratio and the degree of aluminum alloying.
[0008] The arrangement of the grooves and their relationship with the direction of twist determine whether the aforementioned contact interface can be used for reciprocating alternating wind-induced vibration conditions. The reverse inclined planes alternate axially with a period of 2.5mm to 3.5mm, ensuring that both half-cycles of the reciprocating alternating motion receive an increase in normal force. The plastic residual forces of the two sets are opposite in direction and cancel each other out, resulting in alternating loading. The subsequent residual interlayer displacement was 0.9 μm, while that of the single-slope control was 46 μm. Two sets of opposing forces were circumferentially offset by 40° to 50°. The radial climbing forces of the two sets formed a balanced couple on the same cross section, rather than being superimposed in the same direction. The single-sided normal force in the locked state was 34.43 N, while that of the control without circumferential offset was 68.9 N, with a nominal contact pressure of 394 MPa and accompanying zinc layer fracturing. The right-handed helical inclination of the gentle slope was opposite to the left-handed stranding direction of the inner aluminum monofilaments. The circumferential component of the climbing force on the stranded wire had a torque opposite to the unwinding torque of the stranded wire under a 35 kN overhead tension. The net torque of the stranded wire changed from 6.058 N·m without weave to 3.54 N·m, and to 8.58 N·m with the same chiral arrangement. The torsional input of the vertical and torsional coupled dancing was reduced at this stage. The total area of the passivated pressure-bearing surface is limited to 4.0% to 8.0%. The untextured original coating surface between the grooves forms a direct contact bridge between current and tensile force. When the proportion drops to 3.0%, the single-sided normal force increases and the nominal contact pressure reaches 391MPa. When the proportion rises to 10.0%, the interlayer contact resistance increases to 134 and the finished DC resistance increases to 0.0741Ω / km. This proportion range is the overlap area between the allowable contact pressure area and the allowable contact resistance area. Attached Figure Description
[0009] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0010] Figure 1 This is a schematic diagram illustrating the effect of the slope angle on the locking threshold slip and logarithmic decay rate in the embodiments of this application; Figure 2 This is a schematic diagram illustrating the relationship between the percentage of the total area of the passivated pressure-bearing surface and the maximum nominal contact pressure and interlayer contact resistance in the embodiments of this application. Figure 3 This is a schematic diagram illustrating the relationship between the number of alternating loading cycles and the residual interlayer displacement in an embodiment of this application. Detailed Implementation
[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Unless otherwise specified, all raw materials used in the embodiments are commercially available products, and all methods used are conventional methods in the art.
[0012] Example 1 This embodiment provides a wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material. The steel core consists of one central galvanized steel wire and six wedge-lift steel wires twisted in a right-hand direction. The steel wire diameter is 2.50 mm, and the steel cross-section is 34.4 mm². The aluminum single wire has a diameter of 3.22 mm and is twisted in three layers with 10, 16, and 22 wires respectively. The twisting direction from the inside out is left-hand, right-hand, and left-hand, with a pitch ratio of 12, a compression coefficient of 0.93, an aluminum cross-section of 391 mm², an aluminum-to-steel cross-section ratio of 11.37, and a finished outer diameter of 26.82 mm. The unit area zinc layer mass of the wedge-lifting steel wire is 260g / m², the groove depth is 20μm, the gentle slope inclination angle is 7.5°, the steep back wall inclination angle is 78°, the passivation bearing surface transition arc radius is 2.0mm, the axial dimension is 0.50mm, and the circumferential dimension is 0.35mm. The positive and negative groups alternate along the axial direction with a period of 3.0mm, with 4 grooves in each period, and are staggered by 45° along the circumference. The total area of the passivation bearing surface accounts for 5.94%, the spiral tendency of the gentle slope is to the right and the angle with the axis is 12°, and the aluminum protrusion embedment depth is 14μm.
[0013] The preparation method is as follows: 82B steel wire rod with a carbon mass fraction of 0.82% was pickled with hydrochloric acid and then phosphated in a 93℃ pyrophosphate solution for 5 minutes. It was then drawn to a diameter of 2.50 mm using a straight-line wire drawing machine in 9 passes, yielding a steel single wire with a tensile strength of 1410 MPa and an elongation of 3.6%. After alkaline washing, water washing, acid washing, water washing, fluxing, and high-frequency induction drying, it was immersed in a 455℃ zinc bath for hot-dip galvanizing at a wire speed of 24 m / min. The wire was then wiped with an air knife until the zinc layer mass per unit area was 260 g / m². The wire was then cooled with circulating water to obtain a standard galvanized steel wire. Based on a zinc density of 7140 kg / m³, the coating thickness was calculated to be 36.4 μm. A reference galvanized steel wire is passed through a pair of carbide rolling rollers with circumferential cutting edges, with a linear load of 180 N / mm and a running speed of 18 m / min, to roll out a groove with a depth of 20 μm, resulting in a bidirectional wedge-shaped textured steel wire. The residual zinc layer at the bottom of the groove is 16.4 μm. A second finishing rolling process is performed with a linear load of 60 N / mm to process the sharp edge at the top of the gently sloping surface into a passivated bearing surface with a transition arc radius of 2.0 mm, resulting in a wedge-shaped steel wire. A boron-aluminum master alloy is added to molten aluminum at 735℃ at 1.5 times the total mass of titanium and vanadium in the molten aluminum. The mixture is held at this temperature and stirred for 25 minutes, then refined with argon for 20 minutes to remove hydrogen, and slag is removed until the hydrogen content is below 0.12 mL per 100 g of aluminum. The mixture is then continuously cast and rolled at a casting temperature of 690℃ and a rolling inlet temperature of 520℃ to obtain an aluminum rod with a diameter of 9.5 mm and a grain size of 85 μm. After aging at 360℃ for 8 hours, the aluminum monofilament is air-cooled and cold-drawn in 12 passes to a diameter of 3.22 mm, with a total reduction in surface area of 88.5%, yielding an aluminum monofilament with a conductivity of 61.0% IACS, a tensile strength of 178 MPa, and an elongation of 2.1%. The steel core is then stranded on a tubular stranding machine, and the aluminum monofilaments are tightly stranded in three layers. The right-hand spiral tendency of the gently sloping surface is opposite to the left-hand stranding direction of the inner aluminum monofilaments. The aluminum monofilaments plastically fill the grooves, forming aluminum protrusions with an embedding depth of 14 μm, resulting in a wedge-shaped interlocking wire blank. This blank is then stabilized and aged at 180℃ for 3 hours and cooled in the furnace to obtain a steel-cored aluminum stranded wire.
[0014] The performance test results of this embodiment are as follows: DC resistance at 20℃: 0.0724 Ω / km; conductivity: 61.0% IACS; breaking force: 103.6 kN; finished product outer diameter: 26.82 mm. In the vibration table test under the conditions of overhead line tension of 35 kN and wind speed of 4 m / s, the logarithmic decay rate was 0.0142, the locking threshold slip was 4.56 μm, and the single-cycle energy consumption at a single point with a slip amplitude of 2.0 μm was... J. At a slip amplitude of 4.0 μm J, power dissipation per unit length at 20Hz is 69.6mW / m. Single-sided normal force in the locked state is 34.43N, nominal contact pressure is 197MPa. Net torque of the stranded wire is 3.54N·m. Number of repeated bending cycles at the clamp exit until the first strand breaks. Second-rate.
[0015] Comparative test. A conventional compressed steel-cored aluminum stranded wire of the same specification was used. The surface of the steel wire in the steel core had no grooves, and all other structural parameters were the same as in this embodiment. The finished product had an outer diameter of 26.82 mm. The logarithmic attenuation rate was measured to be 0.0061, and the energy consumption per cycle at a single point with a slip amplitude of 2.0 μm was measured. J. At a slip amplitude of 4.0 μm J, net torque 6.058 N·m, number of cycles of repeated bending at the wire clamp outlet until the first strand breaks. The DC resistance at 20°C is 0.0723 Ω / km. Under the condition that the outer diameter and DC resistance are the same, the logarithmic decay rate of this embodiment is 2.33 times that of the control, the number of fatigue cycles is 2.53 times that of the control, and the net torque is 58.4% of that of the control.
[0016] Example 2 This embodiment uses the lower limit combination of the claims. The zinc layer mass per unit area of the wedge-lift steel wire is 240 g / m², the equivalent coating thickness is 33.6 μm, the groove depth is 15 μm, and the residual zinc layer at the bottom of the groove is 18.6 μm. The gentle slope angle is 6.0°, the steep back wall angle is 75°, the passivation bearing surface transition arc radius is 1.5 mm, the axial dimension is 0.45 mm, the circumferential dimension is 0.30 mm, and the single-sided area is 0.135 mm². The forward and reverse groups alternate axially with a period of 2.5 mm and are staggered circumferentially by 40°, with the total area of the passivation bearing surface accounting for 4.0%. The aluminum monofilament has a conductivity of 60.5% IACS, a compaction coefficient of 0.92, and an aluminum protrusion embedment depth of 12 μm. The remaining preparation conditions are the same as in Example 1, except that the rolling line load is reduced to 150 N / mm to match the 15 μm groove depth.
[0017] The test results are as follows: Locking threshold slippage 5.71 μm, logarithmic decay rate 0.0118, single-sided normal force under locking condition 27.35 N, nominal contact pressure 203 MPa, stranded wire net torque 3.92 N·m, DC resistance at 20℃ 0.0730 Ω / km, finished product outer diameter 26.80 mm, alternating loading... The residual interlayer displacement was 1.2 μm after the second salt spray test, and the coating integrity rate was 95% after 1000 hours. When all parameters were taken at their lower limits, the locking threshold slip of 5.71 μm was still higher than the upper limit of the interlayer slip amplitude of the micro-wind vibration of 4 μm. The micro-amplitude section was not locked in advance, and the logarithmic decay rate was still 1.93 times that of the conventional compacted stranded wire (0.0061).
[0018] Example 3 This embodiment uses the upper limit combination of the claims. The zinc layer mass per unit area of the wedge-lift steel wire is 280 g / m², the equivalent coating thickness is 39.2 μm, the groove depth is 25 μm, and the residual zinc layer at the bottom of the groove is 14.2 μm. The gentle slope angle is 9.0°, the steep back wall angle is 81°, the passivation bearing surface transition arc radius is 2.5 mm, the axial dimension is 0.55 mm, the circumferential dimension is 0.40 mm, and the single-sided area is 0.220 mm². The forward and reverse groups alternate axially with a period of 3.5 mm and are staggered circumferentially by 50°, with the total area of the passivation bearing surface accounting for 8.0%. The aluminum monofilament has a conductivity of 61.5% IACS, a compaction coefficient of 0.94, and an aluminum protrusion embedment depth of 16 μm. The remaining preparation conditions are the same as in Example 1, but the rolling line load is increased to 210 N / mm.
[0019] The test results are as follows: Locking threshold slippage is 3.79 μm, logarithmic decay rate is 0.0151, single-sided normal force in the locked state is 41.02 N, nominal contact pressure is 186 MPa, net torque of stranded wire is 3.21 N·m, DC resistance at 20℃ is 0.0719 Ω / km, finished product outer diameter is 26.84 mm, the calculated interlayer contact resistance is 11.4% higher than in Example 1, and the coating integrity rate is 93% after 1000 hours of salt spray. When all parameters are taken at their upper limits, the locking threshold slippage decreases to 3.79 μm, which is close to the upper limit of 4 μm for interlayer slippage amplitude under light wind vibration. Part of the slippage amplitude of 4 μm enters the locking zone. Although the logarithmic decay rate reaches 0.0151, the increase slows down. At the same time, the interlayer contact resistance increases. Therefore, 8.0% is the upper limit of the total area of the passivated pressure-bearing surface.
[0020] Example 4 This embodiment is used to verify the effect of the single variable of the gentle slope angle on the locking threshold slip and logarithmic decay rate. The same steel core structure as in Example 1 is used, with a groove depth of 20 μm, a layout period of 3.0 mm, a circumferential stagger of 45°, bearing surface dimensions of 0.50 mm and 0.35 mm, a total area ratio of 5.94%, a helical angle of 12°, and a reverse-handed twisting direction. Only the gentle slope angle is changed; all other parameters remain unchanged.
[0021] Tilt angle 4.0°, locking threshold slip 8.60μm, logarithmic decay rate 0.0074, single-sided normal force 19.1N in the locked state. Tilt angle 6.0°, locking threshold slip 5.71μm, logarithmic decay rate 0.0121, single-sided normal force 27.4N. Tilt angle 7.5°, locking threshold slip 4.56μm, logarithmic decay rate 0.0142, single-sided normal force 34.4N. Tilt angle 9.0°, locking threshold slip 3.79μm, logarithmic decay rate 0.0150, single-sided normal force 41.0N. Tilt angle 12.0°, locking threshold slip 2.82μm, logarithmic decay rate 0.0139, single-sided normal force 54.6N.
[0022] The mechanism analysis is as follows. The locking threshold slip is determined by the ratio of the product of the initial normal force and the effective constraint stiffness in the wedge-lift direction and the tangent of the inclination angle. The initial normal force is given by the residual compressive stress and the string tension, and is taken as 1.5N. The effective constraint stiffness in the wedge-lift direction is given by the series combination of the flexibility of the aluminum protrusion itself and the flexibility of the outer aluminum wire clamping, and is taken as... N / m. As the tilt angle increases, the radial uplift for the same slip increases, and the threshold shifts downward. At a tilt angle of 4.0°, the threshold of 8.60 μm is much higher than the upper limit of 4 μm for interlayer slip amplitude in light wind vibration. Although the 10 μm to 50 μm slip under gust conditions still falls within the locked zone, the increase in normal force in the small amplitude section is insufficient, the hysteresis loop area is small, and the logarithmic decay rate is only 0.0074. At a tilt angle of 12.0°, the threshold of 2.82 μm falls within the slip amplitude range of light wind vibration. Under conditions with slip amplitudes of 3 μm and 4 μm, locking occurs before the climb is fully developed. The hysteresis loop degenerates from a friction slip type to an approximately linear elastic type, the logarithmic decay rate drops back to 0.0139, and the single-sided normal force rises to 54.6 N, with a nominal contact pressure reaching 312 MPa, approaching the zinc layer fracturing threshold. Therefore, the slope angle is limited to 6.0° to 9.0°. Within this range, the threshold falls between 3.79μm and 5.71μm, which is in the gap between the upper limit of the aerodynamic slip amplitude and the lower limit of the gust slip amplitude.
[0023] See Figure 1 In the figure, the diagonal filled bars represent the locking threshold slippage, and the dotted filled bars represent the logarithmic decay rate. The graph shows that the threshold decreases monotonically with the tilt angle, and the logarithmic decay rate reaches an inflection point at 9.0° and then falls back. Both data points fall within their respective allowable ranges within the 6.0° to 9.0° range; this overlapping range is the origin of the tilt angle range defined in the claims. The shapes of the two groups of bars at 4.0° and 12.0° respectively show that the logarithmic decay rate is insufficient when the threshold is too high and falls back when the threshold is too low, both falling outside the defined range.
[0024] Two additional boundary-crossing controls were set up for Example 4. The single-point, single-cycle energy consumption of the 4.0° tilt angle group at a slip amplitude of 2.0 μm was... J represents 76.3% of Example 1. After 1000 hours of salt spray testing in the 12.0° tilt group, the coating integrity rate dropped to 78%, and sectioning revealed annular pressure cracks in the zinc layer beneath the passivated pressure-bearing surface. Both groups fall outside the scope of the claims.
[0025] Example 5 This embodiment is used to verify the combined effect of four characteristics of the groove: bidirectional alternation, circumferential stagger, tip passivation, and reciprocity. A control system of single characteristics and pairwise combinations is used. The baseline group is the full-element group of Example 1, and each control group only modifies the listed characteristics, while the remaining parameters are completely consistent with Example 1.
[0026] Control group A, with only a single gently sloping surface and no reverse side, had a logarithmic decay rate of 0.0093 and was subjected to alternating loading. The residual interlayer displacement was 46 μm, the coating integrity rate was 92% after 1000 hours of salt spray treatment, and the net torque of the stranded wire was 7.14 N·m. Control group B consisted of forward and reverse groups, but axially adjacent without circumferential offset. The logarithmic decay rate was 0.0121, the residual interlayer displacement was 1.1 μm, the single-sided normal force under the locked state was 68.9 N, the nominal contact pressure was 394 MPa, and the coating integrity rate was 74%. Sectional inspection revealed zinc layer fracturing below the pressure-bearing surface. Control group C consisted of alternating bidirectional and circumferential offset groups, but the top of the gentle slope was not passivated. Under the locked state, the pressure-bearing area was 0.0175 mm², the nominal contact pressure was 1970 MPa, the coating integrity rate was 71%, and after 500 hours of equivalent operation, the logarithmic decay rate changed from the initial 0.0136 to 0.0088. Control group D, with bidirectional alternation, circumferential stagger, and top passivation but with a gently sloping spiral tendency and the same chirality as the inner aluminum monofilament stranding direction, has a logarithmic decay rate of 0.0140 and a net strand torque of 8.58 N·m, which is 2.42 times that of the baseline group (3.54 N·m). Under the simulated galloping conditions of 5 mm icing thickness and 12 m / s wind speed, a vertical and torsional coupling pattern was observed, which was not observed in the baseline group under the same conditions. Control group E, with bidirectional alternation and top passivation but without circumferential stagger and the same chirality, has a logarithmic decay rate of 0.0119, a nominal contact pressure of 391 MPa, a net strand torque of 8.71 N·m, and a coating integrity rate of 73%. The logarithmic decay rate of the reference group is 0.0142, the residual interlayer displacement is 0.9 μm, the nominal contact pressure is 197 MPa, the coating integrity rate is 96%, the net torque of the stranded wire is 3.54 N·m, and the logarithmic decay rate is 0.0140 after 500 hours of equivalent operation.
[0027] Individually, none of the four characteristics can simultaneously meet the requirements for energy consumption stroke, residual displacement, contact pressure, and net torque. Without the reverse group, the residual displacement reaches 46 μm, 51.1 times that of the baseline group. Without circumferential misalignment, the nominal contact pressure is 394 MPa, accompanied by zinc layer fracturing. Without tip passivation, the nominal contact pressure is 1970 MPa, and the logarithmic decay rate decreases with operating time. Without reciprocity, the net torque rises to 8.58 N·m, exhibiting vertical and torsional coupling. When all four characteristics are present, all indicators fall within the permissible range, and the logarithmic decay rate of 0.0142 is the maximum value among all groups; the four characteristics constitute an inseparable combination.
[0028] Example 6 This embodiment is used to verify the influence of a single variable: the proportion of the total area of the passivated pressure-bearing surface. All other parameters are the same as in Example 1, except for the number of grooves per cycle, which is changed to adjust the proportion. Proportion 3.0%, logarithmic decay rate 0.0102, nominal contact pressure in locked state 391 MPa, interlayer contact resistance converted to 96 (based on Example 1's value of 100), coating integrity rate 85% after 1000 hours of salt spray. Proportion 4.0%, logarithmic decay rate 0.0118, nominal contact pressure 203 MPa, interlayer contact resistance converted to 98, coating integrity rate 95%. Proportion 5.94%, logarithmic decay rate 0.0142, nominal contact pressure 197 MPa, interlayer contact resistance converted to 100, coating integrity rate 96%. Proportion 8.0%, logarithmic decay rate 0.0151, nominal contact pressure 186 MPa, interlayer contact resistance converted to 111, coating integrity rate 93%. It accounts for 10.0%, logarithmic decay rate is 0.0153, nominal contact pressure is 181MPa, interlayer contact resistance is 134, coating integrity rate is 89%, and DC resistance at 20℃ is 0.0741Ω / km.
[0029] The mechanism analysis is as follows. The unwoven original coating surface between the grooves is in direct, tight contact with the inner aluminum wire, forming a conduction channel for current and tension. The area ratio of this direct contact bridge is equal to the total area ratio of the passivated bearing surface. When the ratio is 3.0%, the number of bearing surfaces participating in the wedge lifting is insufficient, and the normal force borne by a single surface increases to 1.98 times that under the same locking stroke. The nominal contact pressure of 391 MPa approaches the zinc layer fracturing threshold, and the locking stroke exhibits a discrete pattern with a logarithmic decay rate of only 0.0102. When the ratio is 10.0%, the direct contact bridge area decreases to 90%, the interlayer contact resistance increases to 134, and the finished product's DC resistance changes from 0.0724 Ω / km to 0.0741 Ω / km, exceeding the resistance limit of this specification of wire. Furthermore, the potential difference between the steel core and the aluminum layer presents galvanic corrosion conditions under humid conditions, reducing the coating integrity rate to 89%. Therefore, the total area ratio of the passivated bearing surface is limited to 4.0% to 8.0%.
[0030] See Figure 2 In the figure, hollow circles represent the nominal contact pressure at each percentage, solid squares represent the converted interlayer contact resistance, and horizontal dashed lines represent the zinc layer fracturing threshold. The graph shows that the two data points move in opposite directions: contact pressure decreases as the percentage increases, then jumps sharply to near the threshold at 3.0%, while the converted contact resistance increases sharply after 8.0%. Their respective allowable zones overlap only between 4.0% and 8.0%, and this overlap is the origin of the percentage range defined in the claims.
[0031] Example 7 This embodiment is used to verify the difference in outer diameter and wind load between the present application and the self-damping scheme with interlayer gaps under the same energy dissipation level. The finished product of Example 1 is used as the test group. The control part is a self-damping stranded wire with gaps and the same conductive cross-section of 391 mm². A gap of 0.8 mm is maintained between the steel core and the inner aluminum wire and lubricated with grease. The aluminum wire has a trapezoidal cross-section and the finished product has an outer diameter of 28.4 mm.
[0032] The experimental group had a logarithmic attenuation rate of 0.0142 and a finished product outer diameter of 26.82 mm, while the control group had a logarithmic attenuation rate of 0.0138 and a finished product outer diameter of 28.4 mm. Based on a shape coefficient of 1.1, a wind pressure height variation coefficient of 1.0, and a design wind speed of 30 m / s, the wind load per unit length was calculated as follows: 16.59 N / m for the experimental group and 17.58 N / m for the control group. The experimental group was 5.63% lower in this aspect. After a simulated wire laying test using a traction wheel and wire reel, the gap in the control group decreased from 0.8 mm to between 0.3 mm and 0.5 mm, and the logarithmic attenuation rate became 0.0101. After the same wire laying test, the experimental group had a logarithmic attenuation rate of 0.0141, and the groove depth and aluminum protrusion embedding depth remained unchanged. After the control sample was cycled 200 times between 80°C and -20°C, the grease migrated axially, and the grease residue in the sampling section gap was 62% of the initial value, with the logarithmic decay rate further decreasing to 0.0087. After cycling at the same temperature, the logarithmic decay rate of the test group was 0.0140. The interlayer energy dissipation of this application does not depend on the interlayer cavity, therefore it does not bear the increased outer diameter and wind load caused by the cavity, nor does it bear the changes in the logarithmic decay rate caused by cavity collapse and grease loss.
[0033] Example 8 This embodiment is used to verify residual interlayer displacement, coating integrity, and fatigue performance under long-term service conditions. The test group is the finished product of Example 1, and the control group is control group A of Example 5, namely the single-inclination gently sloping part.
[0034] Alternating loading test. Under conditions of overhead line tension of 35kN, slippage amplitude of 3μm, and frequency of 20Hz, the load was applied at various points. Second-rate, Second-rate, Second-rate, The residual interlaminar displacements were recorded several times. The experimental group displacements were 0.2 μm, 0.4 μm, 0.7 μm, and 0.9 μm, respectively, while the control group displacements were 2.1 μm, 9.8 μm, 31 μm, and 46 μm, respectively.
[0035] See Figure 3 In the graph, the solid line and solid circles represent the experimental group, while the dashed line and hollow triangles represent the control group. The graph shows that the residual displacement of the control group continuously increases on the logarithmic horizontal axis without convergence, while the experimental group... After that, it transitions to a plateau segment, and the two curves... The longitudinal spacing at this point reaches 45.1 μm, and the mutual cancellation of plastic residues between the forward and reverse groups is confirmed by the appearance of this plateau segment.
[0036] Salt spray and vibration coupling test. The test was conducted for 1000 hours under neutral salt spray conditions, during which a reciprocating load with a slip amplitude of 3 μm was applied. The test group showed a 96% coating integrity rate; cross-section revealed a 2.3 μm deep contact imprint on the passivated pressure-bearing surface, with no zinc layer cracking or exposed steel substrate. The control group showed a 92% coating integrity rate; cross-section revealed imprints up to 7.1 μm deep on some pressure-bearing surfaces. The unpassivated control group (Example 5, Control Group C) had a 71% integrity rate, with multiple areas of exposed steel substrate and rust.
[0037] Fatigue test. Repeated bending was applied at the outlet of the suspension clamp until the first strand fractured. Test group... Second, control group Next, conventional compressed steel-cored aluminum stranded wire Next, leave gap self-damping reference piece Second-rate.
[0038] Electrical performance was retested. After all the above tests, the DC resistance of the test group at 20℃ was 0.0726Ω / km, a change of 0.28% compared with the initial value of 0.0724Ω / km, and the conductivity remained at 61.0% IACS Level 1.
[0039] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material, characterized in that, The device comprises a steel core and three layers of aluminum monofilaments stranded around the outer periphery of the steel core. The steel core includes one central galvanized steel wire and six wedge-shaped steel wires. The zinc coating mass per unit area of the wedge-shaped steel wires is 240 g / m² to 280 g / m². The conductivity of the aluminum monofilaments is 60.5% IACS to 61.5% IACS, and the compaction coefficient of the three layers of aluminum monofilaments is 0.92 to 0.
94. The surface of each wedge-shaped steel wire has a groove with a depth of 15 μm to 25 μm, the groove consisting of a gently sloping surface and a steep back wall. The angle between the gently sloping surface and the axis of the wedge-shaped steel wire is 6.0° to 9.0°. The top of the surface is a passivated bearing surface with a transition arc radius of 1.5mm to 2.5mm. The groove includes a positive group with a gentle slope descending in the positive axial direction and a reverse group with a gentle slope descending in the negative axial direction. The positive group and the reverse group are arranged alternately along the axial direction with a period of 2.5mm to 3.5mm and are staggered circumferentially by 40° to 50°. The ratio of the total area of the passivated bearing surface to the surface area of the wedge-lifting steel wire is 4.0% to 8.0%. The spiral tendency of the gentle slope is opposite to the twisting direction of the adjacent layer of aluminum monofilaments. The aluminum monofilaments adjacent to the groove are provided with aluminum protrusions embedded in the groove.
2. The wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 1, characterized in that, The diameter of the central galvanized steel wire and the wedge-lift steel wire is 2.45mm to 2.55mm; the diameter of the aluminum monofilament is 3.18mm to 3.26mm; and the number of the three layers of aluminum monofilaments from the inside out is 10, 16, and 22 respectively.
3. The wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 1, characterized in that, The zinc layer thickness at the bottom of the groove is 15μm to 20μm; the passivated pressure-bearing surface is flush with the maximum outer circumference of the wedge-lifting steel wire.
4. The wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 1, characterized in that, The forward group and the reverse group each have 4 grooves in each cycle; the angle between the steep rear wall and the axis of the wedge-lifting wire is 75° to 81°; the axial dimension of the passivated bearing surface is 0.45mm to 0.55mm, and the circumferential dimension of the passivated bearing surface is 0.30mm to 0.40mm.
5. The wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 1, characterized in that, The angle between the helical tendency of the gentle slope and the axis of the wedge-lifting wire is 10° to 14°; the depth to which the aluminum protrusion is embedded in the groove is 12μm to 16μm.
6. The wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 1, characterized in that, The pitch ratio of the three-layer aluminum monofilament is 11 to 13, and the stranding direction of the three-layer aluminum monofilament is left-handed, right-handed, and left-handed from the inside out, while the stranding direction of the steel core is right-handed; the tensile strength of the aluminum monofilament is 170MPa to 185MPa, and the tensile strength of the wedge-lift steel wire is 1380MPa to 1440MPa.
7. A method for preparing a wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in any one of claims 1 to 6, characterized in that, The process includes the following steps: pickling, phosphating, and multi-pass drawing of steel wire rod with a carbon mass fraction of 0.80% to 0.84%; hot-dip galvanizing the drawn steel wire rod in 455°C zinc bath and wiping with an air knife to obtain a reference galvanized steel wire with a zinc layer mass of 240g / m² to 280g / m² per unit area; passing the reference galvanized steel wire through a rolling roller with circumferential grooves and a linear load of 180N / mm to roll out grooves with a depth of 15μm to 25μm, which are divided into alternating positive and negative groups, to obtain a bidirectional wedge-lift textured steel wire; performing a secondary finishing rolling on the bidirectional wedge-lift textured steel wire with a linear load of 60N / mm, and processing the top of the gently sloping surface of the grooves into a passivated bearing surface to obtain a wedge-lift steel wire; and then hot-dip galvanizing the wire in 735°C aluminum bath. A boron-aluminum master alloy is added and stirred at a constant temperature. The molten aluminum with the added boron-aluminum master alloy is then refined with argon gas to remove hydrogen and slag. The refined molten aluminum is then continuously cast and rolled to obtain an aluminum rod. The aluminum rod is then subjected to an over-aging treatment at 360°C for 8 hours. The over-aged aluminum rod is then subjected to multiple cold drawing passes to obtain aluminum monofilaments. One galvanized steel wire is twisted together with six wedge-lift steel wires to form a steel core. The aluminum monofilaments are twisted in three layers and tightly pressed onto the outer periphery of the steel core. The helical tendency of the gently sloping surface is opposite to the twisting direction of the adjacent layer of aluminum monofilaments. The aluminum monofilaments are plastically filled in the grooves to form aluminum protrusions, resulting in a wedge-lift meshing wire blank. The wedge-lift meshing wire blank is then subjected to a stabilization aging treatment at 180°C for 3 hours to obtain a steel-core aluminum stranded wire.
8. The method for preparing the wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 7, characterized in that, The hot-dip galvanizing process has a wire speed of 22 m / min to 26 m / min, the multi-pass drawing process has 9 passes, and the diameter of the reference galvanized steel wire is 2.45 mm to 2.55 mm; the rolling process has a wire speed of 16 m / min to 20 m / min.
9. The method for preparing the wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 7, characterized in that, The amount of boron-aluminum master alloy added is calculated as 1.4 to 1.6 times the total mass of titanium and vanadium in the molten aluminum; the heat preservation and stirring time is 25 minutes; the argon refining and dehydrogenation time is 20 minutes; the casting temperature of the continuous casting and rolling is 690℃; the rolling inlet temperature of the continuous casting and rolling is 520℃; and the diameter of the aluminum rod is 9.5 mm.
10. The method for preparing the wind-pressure resistant, high-conductivity steel-cored aluminum stranded wire material as described in claim 7, characterized in that, The multi-pass cold drawing consists of 12 passes, the diameter of the aluminum monofilament is 3.18 mm to 3.26 mm, the compaction coefficient is 0.92 to 0.94, the pitch ratio of the three-layer aluminum monofilament is 11 to 13, and the depth of the aluminum protrusion embedded in the groove is 12 μm to 16 μm.